The Effect of Institutional Ownership, Independent Commissioners and Debt Policy on Financial Statement Integrity - Suzan, Leni; Nasution, Melly Juwita (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
There are still many reporting incidents carried out by many parties, making it difficult for investors to make decisions because the integrity of financial reports cannot be trusted. The purpose of this study is to disentangle the partially and simultaneously impacts of institutional ownership, independent commissioners, and debt policy on the reliability of financial statements. This article's secondary data came from the Indonesia Stock Exchange. The population in the study for the years 2017-2021, the sample comprises of 20 coal-focused mining companies trading on the Indonesia Stock Exchange. The study sample was selected by a process of purposive sampling. In this study, the data was analyzed using panel data regression analysis in Eviews 12. The results suggest that independent commissioners, institutional ownership, and debt policy all play significant roles in determining the reliability of financial reporting. Institutional Ownership and Debt Policy partially have a significant effect on the Integrity of the Financial Statements, while the Independent Commissioner does not affect the Integrit y of the Financial Statements. Considering that the adjusted R square rate value is only 0.65 percent and the rest is caused by other variables that may have a greater influence on the application of accounting conservatism, researchers are advised to test other variables that have a greater influence on accounting conservatism, either directly or through use of different proxies such as caution. Management should re-evaluate the role of independent commissioners in managing corporate governance if they want to increase the reliability of financial reports.